Konsep Metode Diskusi dalam Meningkatkan Motivasi Belajar Peserta Didik pada Pelajaran Fiqih - Yasin, Muhammad; Jannah, Siti Sri Fattul (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The aim of this study is to describe the implementation of discussion methods in improving the learning motivation of students in fiqih lessons at Nurul Hikmah MA as well as the supporting and inhibiting factors in using the discussion method. The research method used is a qualitative approach through descriptive methods. This research uses many data collection techniques such as interviews, observations, and documentation. The results of this study show that the concept of discussion method on fiqih lessons in Nurul Hikmah MA uses the division of students into groups to be able to collaborate and engage in discussion. This method significantly increases the motivation of students to learn through the enthusiasm of students. However, in implementing the discussion method there are some supportive and inhibitor factors so that educators can study and review the various existing learning methods. Because not all lessons are suitable for implementation with discussion methods so educators need to have the right learning strategies to facilitate the learning process